Reporting items for systematic reviews and meta-analyses of acupuncture: the PRISMA for acupuncture checklist - Xiaoqin Wang; Yaolong Chen; Yali Liu; Liang Yao; Janne Estill; Zhaoxiang Bian; Taixiang Wu; Hongcai Shang; Myeong Soo Lee; Dang Wei; Jinhui Tian; Bin Ma; et al. (BMC, 2019)
Abstract Background Acupuncture is widely used worldwide, and systematic reviews on acupuncture are increasingly being published. Although acupuncture systematic reviews share several essential elements with other systematic reviews, some essential information for the application of acupuncture is not covered by the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) statement. Considering this, we aimed to develop an extension of the PRISMA statement for acupuncture systematic reviews. Methods We used the PRISMA statement as a starting point, and conducted this study referring to the development strategy recommended by the EQUATOR network. The initial items were collected through a wide survey among evidence users and a review of relevant studies. We conducted a three-round Delphi survey and one-day face-to-face meeting to select items and formulate the checklist. After the consensus meeting, we drafted the manuscript (including the checklist) and sent it to our advisory experts for comments, following which the checklist was refined and circulated to a group of acupuncture systematic review authors for pilot test. We also selected a sample of acupuncture systematic reviews published in 2017 to test the checklist. Results A checklist of five new sub-items (including sub items) and six modified items was formulated, involving content related to title, rationale, eligibility criteria, literature search, data extraction, and study characteristics. We clarified the rationales of the items and provided examples for each item for additional guidance. Conclusion The PRISMA for Acupuncture checklist is developed for improving the reporting of systematic reviews of acupuncture interventions. Trial registration We have registered the study on the EQUATOR network (http://www.equator-network.org/library/reporting-guidelines-under-development/#91).